Possibilities of the Hybrid Method (Three-Phase Scintigraphy-SPECT/CTAngiography) in the Diagnosis and Staging of Acute Lower Limb Ischemia - O. V. Leshchinskaya; N. Y. Kudryashova; I. P. Mikhailov; L. T. Khamidova; L. S. Kokov; I. A. Yeroshkin; B. V. Kozlovsky; E. V. Kislukhina (Неотложная медицинская помощь)
ABSTRACT Acute lower limb ischemia (ALLI) is a limb threatening condition with high risk of adverse outcomes. The timely and proper diagnosis of the severity of limb ischemia is crucial in selecting the optimal treatment method.AIM OF STUDY To evaluate the advantages of hybrid imaging in diagnosis of ALLI, patient selection and its severity in order to choose an optimal revascularization method.MATERIAL AND METHODS we examined 163 patients with grade 1–3A ALLI based on I.I. Zatevakhin et al. classification (2002) on a Discovery 670 NM/CT hybrid device, using X-ray (computed tomographic angiography) and radionuclide method (three-phase scintigraphy/single photon emission computed tomography with osteotropic or perfused radiopharmaceutical).RESULTS CT angiography accurately showed level of acute occlusion as well as distal arterial blood flow in all ALLI cases, thus allowing optimal choice of possible revascularization. CT angiography findings alone did not allow optimal staging of ALLI, which is essential for choosing an optimal revascularization method and were considered as supplementary. Three-phase scintigraphy allowed to differentiate the degrees of ALLI based on the visual picture and calculated data, while studies with osteotropic radiopharmaceutical 99mТс-PYP provided information on viability of affected tissues showing the areas of muscle necrosis, compared to perfused radiopharmaceutical.CONCLUSION 1. CT angiography makes it possible to assess in detail the level and severity of occlusive lesions of the arterial system and study the vascular anatomy of the lower limb to resolve the issue of the possibility of revascularization, and also indirectly characterizes the presence of ischemic changes in soft tissues. 2. The radionuclide method (three-phase scintigraphy with an osteotropic radiopharmaceutical/single photon emission computed tomography), performed in addition to computed tomographic angiography, allows not only to detect the presence of ischemic changes in soft tissues, but also to differentiate the degree of acute ischemia of the lower. 3. The hybrid method (three-phase scintigraphy in combination with computed tomographic angiography) contributes to an objective assessment of the state of blood flow in the lower extremities in acute ischemia, both at the main and at the microcirculatory